Tragedy walks the streets : the French Revolution in the making of modern drama - Buckley, Matthew S., 1965- (Johns Hopkins University Press, 2006)
"Tragedy Walks the Streets challenges the conventional understanding that the evolution of European drama effectively came to a halt during France's Revolutionary era. In this interdisciplinary history of the emergence of modern drama in European culture, Matthew S. Buckley contends that the political theatricality of the Revolution tested and forced the evolution of dramatic forms, supplanting the theater itself as the primary stage of formal development.